Evaluation of resistance rates of enterobacterales to beta-lactam drugs and interpretation of their minimum inhibitory concentrations relative to clinical breakpoints - Uma BM; Neelesh Naik; Rama N.K (Journal of Krishna Institute of Medical Sciences University)
Background: Beta lactam group of antibiotics are one among the most widely used against enterobacterales. There has been an escalation of resistance among cephalosporins, and carbapenems in the recent days. Evaluation of resistance rates and careful selection of drugs based on Minimum Inhibitory Concentration (MIC) aids in effective therapy of infections caused by these resistant strains. Aim and Objectives: To determine the resistance rates of beta lactam antibiotics among enterobacterales, to analyse the relative extent of resistance and susceptibility based on their MIC, relative to their breakpoints, and also to determine MIC 50 and 90. Material and Methods: Study was conducted in a tertiary care hospital in rural Bengaluru from June 2022 to May 2023. A total of 733 clinical isolates from all samples were included in the study. Identification and antimicrobial susceptibility testing was done by VITEK-2 Compact automated system. Results: Based on analysis of MIC among urine samples, resistance rates of 88% for ampicillin, 71% for cefixime and 69% for ceftriaxone was seen. Among other samples 71%,61% and 57% resistance was seen to cefuroxime, ceftriaxone and amoxclav respectively. Least resistance was seen to meropenem (13%) cefoperazone sulbactam (17%) and imipenem (19%). Cefoperazone sulbactam and carbapenems had better susceptibility with MIC 50 less than the susceptible breakpoint. MIC 90 of piperacillin tazobactum and ceftazidime were well above the resistant breakpoint. Conclusion: Understanding the MIC and analysis of susceptibility and resistance of antibiotics will help in rational selection of antibiotics, which may serve as an aid in abating the development of resistant strains. It would be prudent to spare the drugs with MIC 90 above the resistant breakpoint from being included in the empirical panel and should be watchful while using third generation cephalosporins for uncomplicated infections